Conservation biology in sub-saharan Africa - Wilson, John W. (John William), 1979-; Primack, Richard B., 1950-; BC Open Textbook Project; BCcampus (Open Book Publishers, 2019)
"Easy to read, this lucid and accessible textbook includes fifteen chapters that cover a full range of conservation topics, including threats to biodiversity, environmental laws, and protected areas management, as well as related topics such as sustainability, poverty, and human-wildlife conflict. This rich resource also includes a background discussion of what conservation biology is, a wide range of theoretical approaches to the subject, and concrete examples of conservation practice in specific African contexts. Strategies are outlined to protect biodiversity whilst promoting economic development in the region"--BC Campus website.
What is Conservation Biology? -- Introduction to Sub-Saharan Africa -- What is Biodiversity? -- Why Should We Protect Biodiversity? -- The Scramble for Space -- Our Warming World -- Pollution, Overharvesting, Invasive Species, and Disease -- Extinction is Forever -- Applied Population Biology -- Conserving Ecosystems -- Preventing Extinctions -- Biodiversity and the Law -- The Importance of Protected Areas -- Conservation on Unprotected Lands -- An Agenda for the Future -- Appendix A. Selected Sources of Information -- Appendix B. Selected Environmental Organisations -- Appendix C. Obtaining Conservation Funding -- Appendix D. Environmental Calendar.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution 4.0 International license CC BY 4.0.
Includes bibliographical references and index.
Description based on online resource; title from pdf title page (viewed on March 2, 2020).
Keywords: Conservation biology -- Africa, Sub-Saharan.; Electronic books